Pembangunan Aplikasi Permintaan Cuti Berbasis Web Menggunakan Framework Hibernate dan Spring MVC - Pratyaksa Ocsa Nugraha Saian; Yosef Febrianes (Journal of Applied Computer Science and Technology, 2021)
PT XYZ is a subsidiary of one of the largest IT companies in Indonesia which is engaged in Information and Communication Technology (ICT). The company's business unit consists of many aspects, for example in the IT distribution business, providing retail for ICT products, outsourcing IT personnel, designing, installing and maintaining all things related to information technology. In order to run all of its businesses, this XYZ company requires a lot of high quality and high quality human resources, but with the outbreak of the Covid19 pandemic, the work process for PT. XYZ is disturbed because it is done in their respective homes. This results in difficulties for employees in processing administrative matters with the office. One of them is in the matter of taking care of leave permits because the previous leave licensing process was still done manually. The management decided to build an application that can be used by all employees in all subsidiaries. Therefore, the aim of this research is to make an application that can support the administrative needs of employees in the field of leave licensing called "LeaveRequest". This application is designed using the Java programming language with the Spring Boot framework and using the Waterfall software development method. This study found the results that the majority of respondents strongly agree with the design and usability of this application, so it can be concluded that the LeaveRequest application has succeeded in fulfilling the needs in serving the utility of PT. XYZ in work from home condition.